New method for controller-to-controller communication in distributed SDN architecture. (2017) - Benamrane, Fouad; Mamoun, Mouad Ben; Benaini, Redouane
Software defined networking (SDN) is a promising technology that separates the control plane from the data plane in network devices and allows for programmability, flexibility, and efficiency in networks. Adopting this technology for data centres, cloud, and WAN networks could simplify network management. However, SDN was not initially designed for distributed architectures and could not handle a huge amount of data coming from a large network. We aim, in this paper, at providing new architecture composed of multiple SDN controllers, where each controller uses a dedicated interface to communicate with neighbouring controllers. Also, we provide several modes to customise this communication. Last, we show an initial proof-of-concept demonstration of our design.